Oral Potentially Malignant Disorders and Squamous Cell Carcinoma at the Tongue: Clinicopathological Analysis in a Thai Population - Aittiwarapoj, Anchisa; Juengsomjit, Rachai; Kitkumthorn, Nakarin; Lapthanasupkul, Puangwan (European Journal of Dentistry, 2019)
Objective Tongue is regarded as one of the common sites of oral squamous cell carcinoma (OSCC). This study aimed to determine the prevalence and clinicopathological profile of OSCC and oral potentially malignant disorders (OPMDs) at the tongue.Materials and Methods We retrospectively analyzed clinicopathological characteristics of 208 Thai patients diagnosed with SCC and OPMDs at the tongue in the period from 1996 to 2015. Chi-squared test was used to compare differences between patient’s clinical and histopathological features.Results Seventy-eight tongue SCC and 130 tongue OPMD cases were present over the study period. Slight male predominance was found for tongue SCC, while a slight female predominance was present for tongue OPMDs. Both tongue SCC and tongue OPMDs were mostly diagnosed in the old age patients (>40 years old). The majority of tongue SCC and OPMDs occurred at the tip and lateral of the tongue. The most common histologic grading of tongue SCC was well differentiated and no poor differentiation was found in this study. More than a half of tongue OPMDs showed epithelial dysplasia. Both tongue SCC and OPMDs demonstrated no significant correlation between clinical feature and histopathologic diagnosis.Conclusions Tongue SCC and OPMDs were particularly found in the elderly population and frequently developed at the tip and lateral of the tongue. Most of tongue OPMDs, particularly all of tongue erythroplakia, exhibited epithelial dysplasia. For dental practitioners, awareness in the early detection and diagnosis of these tongue lesions should be raised.
Keywords: cancer; erythroplakia; leukoplakia; oral potentially malignant disorders; squamous cell carcinoma; tongue